The impact of COVID-19 government responses on remittances in Latin American countries - Adriana R. Cardozo Silva; Luis R. Diaz Pavez; Inmaculada Martínez-Zarzoso; Felicitas Nowak-Lehmann (Journal of International Development, 2021)
Workers' remittances declined sharply as the COVID-19 pandemic spread in the first half of 2020, rebounding in the second half. This paper analyses the impact of containment and economic support measures on remittances sent to Latin America during 2019–2020 using a gravity model estimated with the Poisson pseudo-maximum likelihood estimator (PPML). Results show that containment measures in receiving countries mainly explain the fall in remittance flows, whereas the effect of economic support measures is not robust. Among the traditional explanatory factors, the business cycle and the real exchange rate in receiving countries explain the subsequent recovery of remittances.
Keywords: 300; COVID-19; Latin America; lockdown; PPML; remittances